Opportunities to Improve Employee Satisfaction Within State and Local Public Health Agencies. Issue 5 (September 2019) - Wisniewski, Janna M.; Jacinto, Corey; Yeager, Valerie A.; Castrucci, Brian; Chapple-McGruder, Theresa; Gould, Elizabeth
Abstract : Context: Public health agencies will likely struggle to staff at necessary levels, given ongoing workforce shortages, the potential for mass retirement, and expanding responsibility. Although the majority of public health workers are satisfied with their jobs overall, it is critical to understand the degree to which they are satisfied and identify factors that contribute to any dissatisfaction that occurs. Objective: This study identified opportunities for public health agencies to improve work environments and, in turn, improve employee satisfaction and retention. Design: Using data from the 2014 Public Health Workforce Interest and Needs Survey, we analyze responses to the survey question, "If you wish, you may provide comments below about your level of job satisfaction." The 2966 responses (2389 from state and 542 from local public health agencies) that indicated a negative disposition were examined to understand employee dissatisfaction. Setting: The survey was administered to a representative sample of state health departments and convenience samples of local health departments. Participants: Responses from employees of state and local health departments are considered. Main Outcome Measures: The most frequently occurring themes overall were identified. In addition, responses describing weaknesses in organizational support (specifically training, communication, workload, and innovation) were summarized. Results: The most frequently occurring themes were as follows: (1) salary, specifically in relation to the merit system, performance evaluation, and workload; (2) job security with emphasis on funding, organizational transformation, and politics/government; and (3) career development related to the merit system, performance evaluation, and management. Respondents also reported opportunities in the areas of training, communication, workload, and innovation to improve satisfaction levels. Conclusions: These findings serve as a call to action for leaders in health departments as well as national public health leaders to remedy the concerns raised in their responses. Some of the solutions are within the realm of public health agency leadership, but some may fall within the realm of governors and public health leaders at the federal level. It is important to share these findings so that appropriate decision makers can address public health workforce retention and recruitment issues in the interest of retaining valuable employees.